Effect of Tube Pass Arrangement on the Thermodynamic Performance of Liquid-vapor Separation Microchannel Condenser - Zhong Tianming; Chen Ying; Zheng Wenxian; Le Wenpu; Luo Xianglong; Yang Qingcheng (Zhileng xuebao)
Liquid-vapor separation microchannel condenser (LSMC) is a novel microchannel condenser. This paper calculated heat transfer coefficient and pressure drop theoretically, and the theoretical results have been verified by experiments. Penalty factor (PF) was employed to evaluate the thermodynamic performance of the LSMC. The results showed number of pass (NP) and tube number per pass (TNPP) have obvious effect on the thermodynamic performance. Under the condition of completely liquid-vapor separation, the 4-tube-pass and 5-tube-pass LSMC showed 5.7% and 13.8% higher heat transfer coefficient than 3-tube-pass LSMC separately. In addition, the pressure drop of 4-tube-pass and 5-tube-pass LSMC is also 23.5% and 138.7% more than 3-tube-pass LSMC separately. In contrast, the TNPP showed a less effect on the heat transfer coefficient and pressure drop. It showed that the NP had a larger effect on simplex performance than the TNPP within the research scope. The thermodynamic performance for the LSMC with completely liquid-vapor separation was better than that with incompletely liquid-vapor separation. Compared with the experimental results, the theoretical heat transfer coefficient showed a maximum deviation of 25.6% and the theoretical pressure drop showed a maximum deviation of 20.8%.